The Influence of Service Quality (Reliability, Responsiveness, Tangibles, Empathy and Assurance) on Student Satisfaction Port Management and Maritime Logistics Study Program Vocational Faculty of Shipping Hang Tuah University - Benny Agus Setiono; Putra, Revian Nico Pradana (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2025)
This study aims to analyze the effect of service quality, comprising reliability, responsiveness, tangibles, empathy, and assurance, on student satisfaction in the Maritime Port Management and Logistics Study Program, Faculty of Vocational Shipping, Hang Tuah University. This research employed a quantitative method with a survey approach, collecting data through questionnaires distributed to 115 students using a saturated sampling technique. The data were analyzed using multiple linear regression analysis. The results reveal that service quality simultaneously has a significant effect on student satisfaction, with a contribution rate of 95.9%. Partially, reliability, responsiveness, tangibles, and assurance have a significant positive effect on student satisfaction, while empathy does not show a significant influence. These findings highlight the importance of improving service quality aspects, particularly tangible elements, to optimize student satisfaction within the Maritime Port Management and Logistics Study Program.